Apprenticeship-based training in neurogastroenterology and motility. (4th March 2018) - Vasant, Dipesh H.; Sharma, Amol; Bhagatwala, Jigar; Viswanathan, Lavanya; Rao, Satish S.C.
ABSTRACT: Introduction : Although neurogastroenterology and motility (NGM) disorders affect 50% of patients seen in clinics, many gastroenterologists receive limited NGM training. One-month apprenticeship-based NGM training has been provided at ten centers in the USA for a decade, however, outcomes of this training are unclear. Our goal was to describe the effectiveness of this program from a trainees perspective. Areas covered : We describe the training model, learning experiences, and outcomes of one-month apprenticeship-based training in NGM at a center of excellence, using a detailed individual observer account and data from 12 consecutive trainees that completed the program. During a one-month training period, 302 procedures including; breath tests (BT) n = 132, anorectal manometry (ARM) n = 29 and esophageal manometry (EM) n = 28, were performed. Post-training, all trainees (n = 12) knew indications for motility tests, and the majority achieved independence in basic interpretation of BT, EM and ARM. Additionally, in a multiple-choice NGM written-test paper, trainees achieved significant improvements in test scores post-training (P = 0.003). Expert commentary : One-month training at a high-volume center can facilitate rapid learning of NGM and the indications, basic interpretation and utility of motility tests. Trainees demonstrate significant independence, and this training model provides an ideal platform for those interested in sub-specialty NGM.